War-related vicarious trauma among healthcare providers in the war-torn tigray, Northern Ethiopia - Hagos Degefa Hidru; Mengistu Hagazi Tequare; Abadi Kidanemariam Berhe; Gidey Gebremeskel Kidane; Yemane Gebremariam Gebre; Mohamedawel Mohamedniguss Ebrahim; Aregawi Gebreyesus; Gebregziabher Berihu Gebrekidan; Reiye Esayas Mengesha; Gebrekiros Gebremichael Meles; Assefa Ayalew Gebreslassie; Bereket Berhe Abreha; et al. (PLoS ONE, 2026)
Background Tigray War, which started in November 2020, has doubled the burden on healthcare professionals, causing both direct violence and indirect effects as they care for trauma survivors. Vicarious trauma refers to harmful changes that occur in professionals’ views of themselves and/or others as a result of deep empathic engagement and repeated exposure to details of trauma survivors. There is insufficient data to determine the prevalence of vicarious trauma among healthcare workers in the region. Therefore, this study assessed the extent of vicarious trauma among healthcare providers working in the war-torn Tigray region of Ethiopia. Method A health facility-based cross sectional study design was used to recruit 2,374 healthcare providers from August to September 2023 in the war affected Tigray region of Ethiopia and the study participants were selected using stratified random sampling techniques. Data were collected using the Open Data Kit (ODK) and exported to SPSS version 23.0 for analysis. Vicarious trauma was assessed using a 7-item standard tool with likert scale responses ranging from very often (5) to rarely (0). The total score from the responses on these 7 items was categorized as low risk (0–14), moderate risk (15–21), high risk (22–28), and extremely high risk (29–35). Ordinal multivariable logistic regression was used to identify the association of various factors with vicarious trauma. Statistical significance was reported when p-value was less than 0.05. Result Prevalence of moderate and above vicarious trauma was revealed as 81.6% (95% CI: 80.0, 83.1). Specifically, the burden was identified as 32.4%, 33.3%, and 15.8% for moderate, high,and extremely high levels of vicarious trauma respectively, with significant variability across the administrative zones of the region. Risk of vicarious trauma increases with increasing age 30–39 years (AOR = 1.3, p-value = 0.002), 40–49 years (AOR = 1.5, p-value = 0.01), 50 years and above (AOR = 2.3, p-value = 0.0001), having a larger family size (AOR = 1.2, p-value = 0.03), among those who live far from their work place (AOR = 1.3, p-value = 0.04), and among those in leadership positions (AOR = 1.5, p-value = 0.0001). Conclusion Healthcare workers in Tigray region experienced high level of vicarious trauma (8 out of 10). This was worse for older workers with larger families, those living and walking farther to work, and those working in heavily conflict-affected central and northwest Tigray. This calls for the government and stakeholders urgently collaborate to provide training on mental resilience, coping strategies, and support resources, offer age-specific psychoeducation, consider adjusting work hours for older employees, support affected employees and their families, improve transportation, and reduce administrative burdens on managers to prioritize staff well-being.